Платоновиот мит за пештерата: над алегорија - Дуев, Ратко (Македонска Академија на Науките и Уметностите, 2019)
A number of interpretations exist concerning Plato’s famous Мyth of the cave, and its allegory, but does the cave also conceal a different meaning in this myth? Cult caves are characteristic of the Minoan civilization during the Middle Bronze Age. A number of such cult caves have been discovered, located far away from populated areas, set high in the mountains, inaccessible during the winter due to the snow and cold weather conditions, and, as such, inhospitable neither for habitation nor for burials, to allow for any analogy to be made with prehistoric cave dwellings and tombs. As such, as far back as the early history of the Aegean, they were, for the Minoans, home of the deities. Plato’s θαυματοποιοῖ (miracle workers or magicians) remind of the priests who, while performing rites, would, throughout the caves, put up figurines, votive gifts, and throw them into natural basins, just like magicians did. The poet has chosen the cave not just as allegory, but, rather, with the intention to also criticize the superstition of the people who sought a divine epiphany there, an entrance into the Underworld, so as to communicate with the souls of the departed. The belief in the Underworld and in the cult caves which are closest to it went, to a large extent, against the teachings of Plato, and for this reason it is my opinion that it was no coincidence that this symbolism of the dark cave was made use of, which could be entered with a torch, and which, the deeper one went into, the more the natural light coming from its entrance faded.
Plato's myth of the cave: looking beyond the allegory